Factors associated with outcome after successful radiological intervention in arteriovenous fistulas: A retrospective cohort. Issue 6 (November 2019) - Manou-Stathopoulou, Sotiria; Robinson, Emily J; Harvey, John Julian; Karunanithy, Narayan; Calder, Francis; Robson, Michael G
Introduction: Arteriovenous fistulas are the best form of vascular access for haemodialysis. A radiological balloon angioplasty is the standard treatment for a clinically relevant stenosis, but the recurrence rate is high. Data on factors associated with recurrence are limited. Methods: A single centre, retrospective analysis was performed for 124 consecutive patients who had successful interventions for dysfunctional arteriovenous fistulae, to examine factors associated with post-intervention patency. Follow-up was at least 1 year for all patients. Variables associated with primary and cumulative patency were pre-specified and assessed using both un-adjusted (univariate) and adjusted Cox proportional hazards models. Analysis was repeated for a subgroup of 80 patients with a single lesion only in order to examine the potential effects of stenotic lesion characteristics on patency. Results: Factors found to have a significant association with poorer outcomes (less time to loss of patency) included thrombosis at the time of intervention and a history of previous intervention. Fistula age (log days) was significantly associated with better outcomes (greater time to loss of patency). Non-white ethnicity, lesion length, and patient age were also significantly associated with accelerated loss of patency. Discussion: The factors we have identified as linked to poor outcome may help to identify patients in whom a balloon angioplasty is unlikely to provide a durable outcome. This may prompt exploring alternative treatment or dialysis options at an early stage.